(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This paper examines inter-state variation in the cluster development of MSME sector in India. The inter-state variations in the parameters of cluster development (namely Net Working En terprise, Employment, Original Value of Plant & Machinery, Market value of Fixed Assets and Gross output) are conceptualized by constructing a comprehensive Index of Cluster Development. Empirical evidences suggest that southern, western, and northwestern and some northern states scores above the average score of all the states. On the other hand, eastern, central and extreme north ern states (like Jammu and Kashmir) are laggard behind in the performance of overall development of MSME clusters. It is therefore predicted that an inclusive cluster development initiatives across all regions would strengthen the process of MSME cluster development in India.